One Step beyond Species Description: Unveiling a Fine-Scale Diversity within the Genus Dzhanokmenia Kostjukov (Hymenoptera: Eulophidae) - Ganbaatar, Bolormaa; Li, Qin; Xi, Ouyan; Cao, Huanxi; Zhu, Chaodong (Insects (Basel, Switzerland), 2024)
Although Chalcidoidea is one of the megadiverse superfamilies in Hymenoptera, numerous species are still being discovered and described. However, the difficulties in delimiting intra- and interspecific variation hinder this process. In this study, DNA barcoding methods using the COI gene were employed to investigate the morphological variation within Dzhanokmenia Kostjukov, 1977. The nuclear locus, 28S D2, was used to infer a phylogeny to gain an understanding of the relationship of Dzhanokmenia with other potentially close genera. Through a preliminary DNA barcode library established here, including eight species, we calibrated the intraspecific variation in certain diagnostic characters for the new species described here, D. brevifunis Ganbaatar & Cao sp. nov. Maximum likelihood results show that Dzhanokmenia is clustered with the genera associated with Tetrastichus, such as Chaenotetrastichus Graham, 1987, Baryscapus Förster, 1856, Tetrastichus Haliday, 1844, and Oomyzus Rondani, 1870 involved in this study. Our results indicate that the species diversity of Dzhanokmenia is understudied and tentatively confirm that Dzhanokmenia has a potential close relationship with Baryscapus. Along with the DNA barcode library, the referenced phylogeny datasets improve the understanding of the systematic position of Dzhanokmenia within the subfamily Tetrastichinae and the definition of this genus in terms of morphology, thereby facilitating species delimitation, discovery, and description within Dzhanokmenia.